2022
DOI: 10.3390/children9071012
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of the Combination of Active Vision Therapy and Occlusion in Children with Strabismic and Anisometropic Amblyopia

Abstract: This retrospective study was conducted to evaluate the efficacy of the combined treatment of occlusion and active vision therapy in a total of 27 amblyopic children, including 14 strabismic and 13 anisometropic cases. For such purpose, changes in distance and near visual acuity as well as in the binocular function was evaluated during a two-year follow-up. In both amblyopia groups, significant improvements were found in distance and near visual acuity in the non-dominant eye (p < 0.001). In the strabismic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Several studies investigated the efficacy of vision therapy [30,32,53,54,61]. A large retrospective study in India analyzed the data of 160 children between 4 and 13 years old who underwent vision therapy with the Bynocs training platform (Kanohi Eye Pvt., Mumbai, India) [53].…”
Section: Vision Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies investigated the efficacy of vision therapy [30,32,53,54,61]. A large retrospective study in India analyzed the data of 160 children between 4 and 13 years old who underwent vision therapy with the Bynocs training platform (Kanohi Eye Pvt., Mumbai, India) [53].…”
Section: Vision Therapymentioning
confidence: 99%
“…Other studies investigated the effectiveness of vision therapy combined (consequently) with occlusion in children [32,61]. They both concluded that the combination of these treatments offers a significant visual gain in both VA and stereopsis, with no regression over long follow-up periods (12 and 24 months, respectively) [32,61].…”
Section: Vision Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to patching, in which the objective is to penalize the dominant eye and to stimulate the amblyopic eye passively, the binocular treatment has the objective of balancing both eyes, leading to simultaneous vision and, consequently, to binocularity [ 9 ]. These binocular treatments are an adjuvant of patching therapies, with improvements in visual acuity when combining both active and passive treatments [ 10 , 11 , 12 ]. Some previous studies have demonstrated that the effectiveness of the binocular option can be comparable to that obtained with patching [ 13 ].…”
Section: Introductionmentioning
confidence: 99%